(untitled) (Annual of the Faculty of Philosophy in Skopje, 2009)
The following article analyzes the globalization processes and their historical development. The development itself has long and dramatic history, although its evolution line was not continuous, but had interruptions that discontinued it. Nevertheless, the globalization processes orginated from the oldest human groups through archaic empires, up to the present global society.